2019
DOI: 10.3389/fpls.2019.01210
|View full text |Cite
|
Sign up to set email alerts
|

Heritable Changes in Physiological Gas Exchange Traits in Response to Long-Term, Moderate Free-Air Carbon Dioxide Enrichment

Abstract: Atmospheric carbon dioxide ([CO2]) concentrations significantly alter developmental plant traits with potentially far-reaching consequences for ecosystem function and productivity. However, contemporary evolutionary responses among extant plant species that coincide with modern, anthropogenically driven [CO2] rise have rarely been demonstrated among field-grown plant populations. Here we present findings from a long-term, free-air carbon dioxide enrichment (FACE) study in a seminatural European grassland ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Substantial variation among accessions in response to flooding suggests that in the future, breeding may play an important role to improve the resilience of perennial ryegrass to flooding. Holohan et al (2019) showed an improvement in ecological adaptation of grassland species by selection in just a few generations. Detailed ecophysiological studies are necessary to determine the optimal water saturation of soil types for perennial ryegrass and the point in the physiology of the species from where excess water will be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variation among accessions in response to flooding suggests that in the future, breeding may play an important role to improve the resilience of perennial ryegrass to flooding. Holohan et al (2019) showed an improvement in ecological adaptation of grassland species by selection in just a few generations. Detailed ecophysiological studies are necessary to determine the optimal water saturation of soil types for perennial ryegrass and the point in the physiology of the species from where excess water will be detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…The measurements in these natural habitats demonstrated a negative response of this mesophytic species to environmental stress in the dry and hot steppe habitat (Iljin, 1916). Holohan et al (2019) measured leaf gas exchange in G. pratense grown in a free‐air carbon dioxide enrichment (FACE) field experiment in a floodplain meadow near Giessen in Germany (Jäger et al, 2003). Plants grown at ambient (400 ppm) and elevated (480 ppm) levels of CO 2 for 17 years reacted differently to the experimental step increase in CO 2 concentration from 200 to 2000 ppm.…”
Section: Structure and Physiologymentioning
confidence: 99%
“…This unique physiological response was persistent among offspring and was irreversible in at least a single generation even when returned to growth at 400 ppm [CO 2 ] in growth chambers. However, the ability to increase WUEi does not necessarily translate into an ecological advantage for the species (Holohan et al, 2019).…”
Section: Structure and Physiologymentioning
confidence: 99%